Distribution and factors associated with urogenital schistosomiasis in the Tiko Health District, a semi-urban setting, South West Region, Cameroon - Green, Adeline Enjema (Infect Dis Poverty, 2021)
BACKGROUND: Increased risk of schistosomiasis in peri-urban and urban towns is not uncommon. An epidemiological survey was carried out in the Tiko Health District (THD), an unmapped transmission focus for urogenital schistosomiasis (UGS), to assess the distribution, intensity, and risk factors associated with the occurrence of UGS. METHODS: In this cross-sectional survey, 12 communities were purposively selected from four health areas (HAs) (Likomba, Holforth, Holforth-Likomba, and Mutengene) in South West Region of Cameroon between June and August 2018. Consenting individuals were enrolled using a convenient sampling technique and administered a semi-structured questionnaire to document information on socio-demographic and water contact behaviour. Urine samples were examined for Schistosoma haematobium infection using test strip, filtration, and microscopy methods. Bivariate and binary logistic regression analyses were used to identify predictors of infection. RESULTS: The overall prevalence of UGS in Likomba, Holforth-Likomba and Holforth was 31.5% [95% confidence interval (CI): 28.3–34.8] with geometric mean (GM) egg count of 28.7 (range: 2–450) eggs per 10 ml of urine. S. haematobium infection was not found in Mutengene HA. Infection was unevenly distributed among the HAs, Holforth-Likomba and Holforth being the most and least affected, respectively. The prevalence of infection varied (P < 0.001) among the affected communities, ranging from 12.0 to 56.9%. Infection status of the community related positively (P < 0.001) with proximity to stream (< 100 m), the degree of contact with water and number of improved water sources. Younger age group (5–14 years) [adjusted odds ratio (aOR): 3.7, 95% CI: 1.1–12.2] and intense water contact (degree II) (aOR: 5.2, 95% CI: 3.4–8.1) were associated with increased risk of infection. Similarly, significantly higher egg load was observed among younger aged groups (P = 0.02) and those who carried out intense water contact activities (P < 0.001). CONCLUSIONS: Generally, THD is a moderate risk endemic focus for UGS but prevalence higher than 50.0% was observed in some communities. These findings warrant immediate mass chemotherapy with praziquantel to reduce morbidity. Provision of portable water and health education are proposed measures to reduce and eventually eliminate transmission in the area. GRAPHIC ABSTRACT: [Image: see text] SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s40249-021-00827-2.